ULTRASOUND EXAMINATION OF THE LOCOMOTOR SYSTEM IN THE DIAGNOSIS AND MONITORING OF DISEASE ACTIVITY IN JUVENILE ARTHRITIS - D. L. Alekseev; I. P. Nikishina (Научно-практическая ревматология)
Juvenile arthritis is the most common group of childhood rheumatic diseases, the dominant manifestation of which is chronic progressive joint inflammation showing the considerable variability of clinical presentations and the possibility of different nosological outcomes. Diagnosis and monitoring of disease activity in juvenile arthritis, unlike inflammatory joint diseases in adults, are attended with great difficulties in the interpretation of clinical symptoms and radiological findings. One of the most popular current technologies of musculoskeletal visualization is ultrasonography that has become an integral part of a pediatric rheumatology practice. Based on the data available in the literature and their own experience of long-term daily use of ultrasound diagnosis, the authors present current approaches to using the ultrasound diagnostic technique in patients with juvenile arthritis, by taking into account the features of child development.